Faktor-Faktor Penentu Asupan Kalori dalam Diet pada Penderita Diabetes Gestasional: Analisis PLS-SEM Terintegrasi - Ruku, Denny Maurits (NUTRIX, 2026)
Dietary intake plays a critical role in metabolic health, particularly among people with Gestational Diabetes Mellitus, where inappropriate nutritional patterns may increase the risk of adverse pregnancy outcomes. This study aimed to examine the determinants of dietary caloric intake among individuals with gestational diabetes using an integrated structural model. A cross-sectional study was conducted using secondary data from a publicly available dataset on the Kaggle platform (n = 5,165). Variables included body mass index (BMI), glycated hemoglobin (HbA1c), lipid profile, metabolic indicators, blood pressure, and age. Data were analyzed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with bootstrapping. Measurement model evaluation was conducted only for multi-indicator constructs using composite reliability, average variance extracted (AVE), and discriminant validity (HTMT), while single-indicator variables were treated as observed variables. The model demonstrated strong explanatory power (R² = 0.925). Lipid profile exhibited the strongest positive association with dietary intake (β = 0.769, p < 0.001), followed by BMI (β = 0.182, p < 0.001). Age showed a small negative effect (β = -0.062, p < 0.05), whereas glycemic control, metabolic factors, and blood pressure were not statistically significant.  Dietary intake among people with gestational diabetes is primarily influenced by lipid and anthropometric factors, highlighting the importance of metabolism-focused nutritional interventions. Asupan makanan memainkan peran penting dalam kesehatan metabolik, khususnya pada penderita Diabetes Gestational, di mana pola nutrisi yang tidak tepat dapat meningkatkan risiko hasil kehamilan yang buruk. Studi ini bertujuan untuk meneliti faktor penentu asupan kalori makanan pada penderita diabetes gestasional menggunakan model struktural terintegrasi. Studi potong lintang dilakukan menggunakan data sekunder dari dataset Kaggle yang tersedia untuk umum (n = 5,165). Variabel yang digunakan meliputi indeks massa tubuh (IMT), HbA1c, profil lipid, indikator metabolik, tekanan darah, dan usia. Data dianalisis menggunakan Partial Least Squares Structural Equation Modeling (PLS-SEM) dengan bootstrapping. Evaluasi model pengukuran dilakukan hanya pada konstruk multi-indikator menggunakan composite reliability, average variance extracted (AVE), dan discriminant validity (HTMT), sementara variabel indikator tunggal diperlakukan sebagai variabel teramati. Model menunjukkan daya penjelas yang kuat (R² = .925). Profil lipid menunjukkan hubungan positif terkuat dengan asupan makanan (β = .769, p < .001), diikuti oleh IMT (β = .182, p < .001). Usia memiliki efek negatif yang kecil (β = -.062, p < .05), sedangkan kontrol glikemik, faktor metabolik, dan tekanan darah tidak signifikan secara statistik. Asupan makanan pada penderita diabetes gestational terutama dipengaruhi oleh faktor lipid dan antropometrik, yang menyoroti pentingnya intervensi nutrisi yang berfokus pada metabolisme.